T cell‐based targeted immunotherapies for patients with multiple myeloma. Issue 8 (19th September 2014) - Wang, Lei; Jin, Nan; Schmitt, Anita; Greiner, Jochen; Malcherek, Georg; Hundemer, Michael; Mani, Jiju; Hose, Dirk; Raab, Marc S; Ho, Anthony D.; Chen, Bao‐an; Goldschmidt, Hartmut; et al.
<x xml:space="preserve">Abstract</x> Despite high‐dose chemotherapy followed by autologs stem‐cell transplantation as well as novel therapeutic agents, multiple myeloma (MM) remains incurable. Following the general trend towards personalized therapy, targeted immunotherapy as a new approach in the therapy of MM has emerged. Better progression‐free survival and overall survival after tandem autologs/allogeneic stem cell transplantation suggest a graft versus myeloma effect strongly supporting the usefulness of immunological therapies for MM patients. How to induce a powerful antimyeloma effect is the key issue in this field. Pivotal is the definition of appropriate tumor antigen targets and effective methods for expansion of T cells with clinical activity. Besides a comprehensive list of tumor antigens for T cell‐based approaches, eight promising antigens, CS1, Dickkopf‐1, HM1.24, Human telomerase reverse transcriptase, MAGE‐A3, New York Esophageal‐1, Receptor of hyaluronic acid mediated motility and Wilms' tumor gene 1, are described in detail to provide a background for potential clinical use. Results from both closed and on‐going clinical trials are summarized in this review. On the basis of the preclinical and clinical data, we elaborate on three encouraging therapeutic options, vaccine‐enhanced donor lymphocyte infusion, chimeric antigen receptors–transfected T cells as well as vaccines with multiple antigen peptides, to pave the way towards clinically significant immune responses against MM.